Accountability on Sustainability in Central and Eastern Europe: An Empirical Assessment of Sustainability-Related Assurance - Oleh Pasko; Inna Balla; Inna Levytska; Nataliia Semenyshena (Comparative Economic Research. Central and Eastern Europe, 2021)
The paper explores how companies from Central and Eastern Europe adopt assurance practices to provide accountability for sustainability. Drawing on modified coding rules from prior research, a conventional content analysis of 36 assurance statements companies from nine countries was conducted. The results imply differences in the content of reports, processes, and implementation of the standards. Exclusively large and multinational enterprises from the energy sectors domiciled in Poland and Hungary are a typical portrait of a company from the study's sample, striving to issue and assure sustainability reporting. Of the nine countries represented in the study, sustainability assurance statements of companies from Poland, Hungary, and Romania tend to excel in terms of quality. The vast majority of assurance providers belong to the Big Four, who use ISAE3000 as opposed to AA1100AS. Yet, irrespective of the assurance provider type, stakeholders are neglected. It is argued that just transferring the experience of financial auditing to the field of sustainability, which, by and large, has taken place, is not an option. Authors state that following this route, we are heading in the wrong direction, and in technical terms, the wider proliferation of AA1100AS and its principles, with greater emphasis on reasonable assurance as opposed to the limited and enhanced role of stakeholders, are vital to get back on track. The paper contributes to the emerging literature on accountability standards and stresses the need to enhance sustainability-related assurance.
Keywords: Q56; M42; O44; O13; O57; 330; sustainability reporting; assurance statement; GRI; corporate social responsibility; reporting; auditing